Lung Cancer and Autoimmune Disorders - Pokorski, Mieczyslaw (Advances in Experimental Medicine and Biology, 2015)
Lung cancer and autoimmune diseases are complex entities in that they involve gene disturbance, gene polymorphism, and impaired gene repair mechanisms. The volume focuses on altered gene expression in tumor processes and in chronic autoimmune disorders. The chapters discuss the biological rationale for novel disease protein markers, present relevant clinical results, and give some diagnostic and therapeutic tips.